(untitled) (Journal of Applied Science and Engineering A, 2022)
In this work, the influence of catalyst preparation temperature on its structure was investigated. We have synthesized 12 different Ni/ZrO2 catalysts by varying the calcination temperature, time, and active metal content, and these catalysts will be further used in the carbon dioxide methanation reaction. Structure and properties of the catalysts were determined using XRD and SEM analysis. Therefore, Ni content of the catalysts were measured by ICP-OES. Regarding to the crystal size calculation using XRD data by Scherer equation, when calcination time was increased the average crystal size of nickel oxide was decreased from 42.38 nm to 38.93 nm whereas it decreased to 39.23 nm when the calcination temperature was increased. This shows that the distribution of active metals in the catalyst increases when the heat treatment parameters are increased. In addition, it can be assumed that the activity of the catalyst can be enhanced when the calcination temperature and time were increases.